MODELS OF STATE SUPPORT OF CULTURE IN THE RUSSIAN FEDERATION AND PROBLEMS OF THEIR FUNCTIONING - Nadezhda A. Kaverina (Вестник Российского экономического университета имени Г. В. Плеханова, 2017)
A new view on state as a carrier of long-term interests of society advances as a principle argument in substantiating the state support of culture its strategic importance in social and economic development of the country. The article shows three models of state support of the culture sphere: subsidiary, investment and stimulating. The author describes mechanisms and resources of each model of financing. She analyzed the volume of financing culture at the expense of state funds from 1991 to 2015 and showed a break of the positive prolonged dynamics of culture financing in 2015. Causes of cutting state expenditure on culture were identified. The shift from ‘state-Maecenas’ to ‘state-investor’ was acknowledged. It was stipulated mainly by the absence of favorable institutional environment in the field of culture.